2022
DOI: 10.1186/s13756-022-01162-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes about antibiotic resistance in the general public and general practitioners in France

Abstract: Background During the last 20 years, France has taken important steps to tackle antibiotic resistance. These include national awareness campaigns for the general public, and supporting changes in terms of antibiotic prescription for healthcare practitioners. To prepare the upcoming 2022/2023 campaign, we conducted two surveys to assess (1) the general public’s knowledge, attitudes and behaviours regarding antibiotics and (2) the perceptions and practices of general practitioners (GPs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A 2021 study in Turkey revealed that 37% of parents with a child under 18 years old believed that antibiotics could cure infections caused by viruses [24]. In France, only about half of the participants in the general public knew that antibiotics only target bacteria, regardless of whether they were parents with a child ≤6 years old or not [25]. A similar finding was observed among Italian parents, among which 33% declared that antibiotics were useful for treating viral infections [26].…”
Section: Discussionmentioning
confidence: 89%
“…A 2021 study in Turkey revealed that 37% of parents with a child under 18 years old believed that antibiotics could cure infections caused by viruses [24]. In France, only about half of the participants in the general public knew that antibiotics only target bacteria, regardless of whether they were parents with a child ≤6 years old or not [25]. A similar finding was observed among Italian parents, among which 33% declared that antibiotics were useful for treating viral infections [26].…”
Section: Discussionmentioning
confidence: 89%
“…Although the students are aware of the severity and consequences of the increase in antibiotic resistance, they view it as a medium-to-long-term problem. They are uncertain about the extent to which it currently affects their healthcare environment, a belief shared by medical professionals across different fields [ 25 , 26 , 27 ]. Similar findings were reported in a systematic review, which revealed that students acknowledge antibiotic resistance as a global public health concern but do not express concern about its impact in their immediate workplace or learning environment, such as their teaching hospital [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in England found that 38% of the public asked physicians to prescribe antibiotics ( 13 ). In a study conducted in France, 39% of physicians stated that their patients frequently asked them to prescribe antibiotics ( 18 ). In our study, this rate was 28%.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in Türkiye, the rate of awareness of the rational use of antibiotics was reported to be 8.2%, and the rate of having heard about antibiotic resistance was 32.5% (4,8). Studies indicated that 38% to 69% of the public was aware of antibiotic resistance (14,(16)(17)(18). In a study by Lim et al, the rate of participants who believed that antibiotic resistance would cause treatment failure in severe infections was 7% (14).…”
Section: Discussionmentioning
confidence: 99%